Creep Behavior of Red-Clay Under Triaxial Compression Condition - Xue, Kaixi; Wang, Shengfu; Hu, Yanxiang; Li, Mingdong (Frontiers in Earth Science, 2020)
To investigate the shear strength and creep behavior of red-clay, laboratory experiments were conducted and the experimental results were compared with available theoretical creep models. Based on the consolidated-drained (CD) triaxial tests results, internal friction angle and cohesion of the red clay soil were 21.5° and 61.1 kPa, respectively. Three different confining pressures were set up to conduct the creep tests using multi-stage loading. The overall creep curves exhibited stepped stress-strain behavior. The creep behaviors were remarkably different for the soils tested with three different confining stresses. The post-creep failure mode of all the red clay samples exhibited drum shaped parabolic bulging with predefined shear planes. The experimental results were compared with three different types of creep models used in practice. Among the verified results, the Burger’s Model showed better fitting with the experimental data compared to the other models. An experimental result based empirical equation has also been developed, which fits well with the experimental results obtained from the tested red clay samples. The results of this study will be helpful to evaluate the long-term shear strength and deformation of red clays subjected to various structural loadings.